Research on Oil-based Drilling Fluid for Protecting Oil Reservoir - Xiao Guo, Ting Huang; Wang, Zhihong (International Journal of Science and Engineering Invention, 2015)
Adopt a set of diesel-base drilling fluid system. Laboratory experiment shows that the diesel-base drilling fluid is of good rheological property and high resistance of salt,calcium, water pollution , and is a good protector of the oil and gas reservoir, which can solve the problem of strong water sensitivity and easy to collapse.